Characterization of the Na+/HCO3¯ cotransport in human neutrophils - Giambelluca, Miriam Soledad (2014)
Background: Bicarbonate transport has crucial roles in regulating intracellular pH (pHi) in a variety of cells. The purpose of this study was to evaluate its participation in the regulation of pHi in resting and stimulated human neutrophils. Methods: Freshly isolated human neutrophils acidified by an ammonium prepulse were used in this study. Results: We demonstrated that resting neutrophils have a bicarbonate transport mechanism that prevents acidification when the Na+/H+ exchanger is blocked by EIPA. Neutrophils acidified by an ammonium prepulse showed an EIPA-resistant recovery of pHi that was inhibited by the blocker of the anionic transporters SITS or the Na+/HCO3¯ cotransporter (NBC) selective inhibitor S0859, and abolished when sodium was removed from the extracellular medium. In western blot and RT-PCR analysis the expression of NBCe2 but not NBCe1 or NBCn1 was detected in neutrophils Acidified neutrophils increased the EIPA-insensitive pHi recovery rate when its activity was stimulated with fMLF/cytochalasin B. This increase in the removal of acid equivalents was insensitive to the blockade of the NADPH oxidase with DPI. Conclusion: It is concluded that neutrophils have an NBC that regulates basal pHi and is modulated by chemotactic agents.